Komposisi Jenis Zooplankton Di Perairan Sungai Je’neberang Sungguminasa Kec. Somba Opu Kab. Gowa - Ernawaty, .; Sitti, Saenab; Rabanai, . (Fakultas MIPA UNM, 2011)
A research report of the composition of zooplankton species on Je’neberang river in Sungguminasa regency Somba Opu sub district. The objective of this research was to find out the composition of zooplankton species on Je’neberang river in Sungguminasa regency Somba Opu sub district. The sample was taken between 20.00-22.00 wita by using plankton net number 25 during thee days. The parameter used was biology, physics and chemistry parameters. This research employed descriptive method. It symbolized the composition of zooplankton species on Je’neberang river in Sungguminasa regency Somba Opu sub district on the three monitoring by using Sedgwick rafter method (SRC). It was monitored under binocular microscope. The finding of the research showed that there were 26 species of zooplankton included Arthopod, Annelid, Asteroid, and Cnidaria filus. The Composition of zooplankton in the three monitoring was dominated by crustacean class. The abudance of zooplankton was 54 ind/m3.- 702 ind/m3. Based on the variety and dominan index, it can be concluded that Je’neberang river had the low variety of zooplankton.